The level of impact of using social media in spreading awareness about rheumatic diseases among patients - Rifaei, Sufian; Sumadi, Adnan; Al-Jaraideh, D.; AlJbour, AlJbour; T. Rumman, Mumen (Journal of Neonatal Surgery, 2025)
Social media is a promising strategic tool for promoting health awareness in the current digital age. This study aims to evaluate its impact on disseminating accurate information about rheumatic diseases, while providing practical recommendations for improving awareness strategies in line with the health needs of the community. The descriptive analytical approach was adopted. The questionnaire tool was distributed electronically to the study community, which included patients participating in the Jordanian Rheumatology pages. The final study sample was (185) individuals. The study concluded that there is a positive impact of social media on patients' awareness of rheumatic diseases.